Analysis of Figurative Language in Boywithuke Song Lyric’s - Mangaraja, Jeli Elvira; Pasaribu, Arsen Nahum; Sembiring, Rony Arahta (Institut Agama Islam Negeri Palopo, 2023)
This research is related to Figurative Language Analysis in Boywithuke song lyrics. The purpose of this study was to identify the types of figurative words found in 20 BoywithUke songs and to explain the meanings contained in the songs. Data sources were taken from 20 popular singers and musicians from American singers and musicians with the record label Republic. The twenty are toxic, two moons, long drives, lovesick, haha,hi, out of tune, IDGAF, understand, wafers, shy, bad luck, lovely, hazel eyes, heart of ice, far away, scared of the dark, she said no, i wan't let you go, contigo, blurry nights. The principles used in this study are quoted from the principles of figurative language put forward by Keraf (2009). The mode used in this study is a qualitative mode. Starting with listening to the song, then analyzing song lyrics that contain figurative language and recording related data. From this study, fourteen kinds of figurative language were found from twenty BoywithUke song lyrics, namely simile 8.5%, metaphor 19.3%, allegory 6.3%, personitification 6.3%, allusion 0.5%, eponym 0, 2%, epithet 0.2%, synecdoche 14.3%, metonym 1.6%, antonomasia 12.9%, hypalase 10.4%, irony 12.7%, satire 1.3%, pun 4.6% of the total types of figurative language according to Keraf's theory (2009).